ELECTRONIC VOTING USING DECENTRALIZED SYSTEM BASED ON ETHEREUM BLOCKCHAIN - Fajri Fadli; Singgih Jatmiko; Missa Lamsani (STMIK JAKARTA STI&K, 2020)
Electronic Voting Using Decentralised System Based On Ethereum’s Blockchain is a system made in the form of application used for Electronic Voting. This is done to solve the current problem on conventional electronic voting system where the integrity of the data can’t be ascertain and the result of the vote can be tampered malicious actors. To solve this problem, an electronic voting system will be built that store the data of election results on blockchain to ensure the integrity of the data. The creation of the system involves using the Solidity language, a Turing Complete programming language used on Ethereum. Source code that will be run will first need to be compiled into Bytecode, which will then in turn run on Ethereum Virtual Machine. The finished program will then be decentralised using Blockchain. p margin-bottom: 0.1in; direction: ltr; line-height: 115%; text-align: left; p.western font-family: "Calibri", serif; p.cjk font-family: "??"; p.ctl a:link color: rgb(0, 0, 255);